Study on vitamin D status and determination of optimum vitamin D level based on bone turnover markers in Kota Bharu, Kelantan - Muda, Noor Bayani Che (2017)
Background: There is no optilnmn level or threshold that has been clearly established to define whether there is adequate store of vitamin D in the body for general bone health. Therefore, our study is to determine the optimum level of vitamin D for maintenance of healthy skeleton based on bone remodelling process. Methods: This was a cross sectional study involving healthy adult population in Kota Bharu, Malaysia, aged 18-50 years. We measured serwn 25(0H)D, serum parathyroid hormone (PTH), serum C-terminal telopeptide of type 1 collagen ( CTX) and Procollagen 1 Intact N-Terminal (P1NP) in 120 healthy adult from 6 sub districts that had been selected by multi stage sampling ( 64 males, 56 females). Results: The mean of vitamin Din this study was 23.50 (±8.74) nmol/L and there was significant difference of vitamin D betvveen gender (26.81±8.3 nmol/L and 19.72±7.68 nmol/L males and females respectively), p value < 0.001. More than 50% of female subjects had vitamin D less than 20 nmol/L, while only 20.3% of male subjects had vitamin D below 20 nmol/L. Based on LOESS plot, the bone turnover markers showed plateau result at vitamin D level of 3 5 nmoi!L for CTX and 20 nmoi/L for p 1 NP. Then, at vitamin D level of 20 nmol/L there is a step decrease of PTH level. Conclusion: The mean of vitamin D among general healthy population in Kota Bharu was 23.50nmoi/L. Based on inspection of LOESS plot for CTX, PlNP and PTH versusvitamin D level, we concluded that vitamin D level between 20 nmol/L to 35 nmol/L is considered sufficient to maintain healthy skeleton.